VOLATILITAS DAN RISIKO HARGA CABAI MERAH KERITING (SUATU KASUS DI PASAR BARU KRANGGOT KOTA CILEGON) - Ahmad Naziullah; Aris Supriyo; Ratna Mega Sari; Suherman Suherman (JURNAL AGRIBISNIS TERPADU, 2021)
Chili is one of the irreplaceable commodities for food necessity. Pasar Baru Kranggot is a market for farmers to necessity Cilegon people supplied. Farmers for harvest supplied to be a price taker and it makes them have fewer revenue sales. Government policy for producer have not followed by policy on the market and that shows presence price fluctuation on curly red chili. That’s price fluctuation in the market is that causes price risk on curly red chili commodity. Research and data retrieval conducted in Pasar Baru Kranggot, the method of this research is use the ARCH-GARCH model and Value at Risk (VaR). The findings of this study are indicated that the best model is ARCH (1) which is mean that chili price is affected by the previous week’s volatility. The price risk for one week’s sales later is the amount of 24.8% and in two weeks 35.07%. The prevention to reduce the price risk for farmers can be done by building cooperation/partnership with the start-up/marketing industry, planting time and planting patterns, cooperated with pesticide company and contract systems. The government effort can do to reduce price risk is production of warehouses, the setup of agents/distributors in supplying, the openness of information for farmers and the market, the treatment and the risk building of farmers.